THE USE OF AUTHENTIC MATERIALS IN ENGLISH LANGUAGE CLASSROOMS: BRIDGING THE GAP BETWEEN THEORY AND REAL- WORLD COMMUNICATION - Odilova Zuhrakhon, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  research  examines  the  pedagogical  significance  of  integrating  authentic materials  into  the  English  as  a  Foreign  Language  (EFL)  classroom.  Authentic materials—ranging  from  newspapers,  podcasts,  and  brochures  to  films  and advertisements—provide learners with exposure to the language as it is naturally used by  native  speakers.  The  study  evaluates  how  these  materials  influence  student motivation,  cultural  competence,  and  linguistic  flexibility.  By  comparing "pedagogical" (textbook-based) texts with "authentic" sources, the research argues that the latter is essential for developing true communicative competence. The paper also outlines strategies for curriculum developers to select and adapt authentic content for diverse proficiency levels.